Ladle-treated high manganese steel reinforced by Cr7C3 phase. (4th March 2017) - El Fawkhry, Mohamed Kamal
Abstract: This research programme was designed to study the effect of chromium addition on the characteristic properties of Hadfield steel that has been produced by using the ladle treatment process. Chromium-containing ladle-treated Hadfield steel and chromium-free ladle-treated Hadfield steel have been produced, comparing with the Hadfield steel that has been produced by the conventional process. It has been found that chromium addition has a significant effect on the characteristic properties of the ladle-treated Hadfield steel. For instance, wear abrasion resistance was enhanced approximately five times much higher than conventional Hadfield steel. Moreover, an industrial trial indicates that chromium-containing ladle-treated Hadfield steel has significant benefits from the perspective of performance, and production cost as well.